Note from the Editor-in-Chief - Elivo, Ryan (Consilience, 2015)
Dear Readers, It is my absolute pleasure to present the 13th Issue of Consilience: The Journal of Sustainable Development. Our Editorial and Managing Boards have worked assiduously to bring you our longest and most ambitious issue yet, at 16 articles comprised of a cumulative 346 pages. This upsurge in submissions is a reflection of the rising prominence of the global conversation on sustainable development, with the year 2015 ushering in the rollout of the Sustainable Development Goals and the 21st Conference of Parties, with the goal of realizing a legally binding treaty to lower greenhouse gas emissions. Issue 13 features a variety of topics spanning myriad subjects and geographical regions, all unified around three questions that have implications for the future of sustainable development: (1) How have the economic and technocratic rationalities that have thus far defined development changed, and how must they continue changing to reflect the realities of our world? (2) Have the frameworks, solutions, and priorities that have been implemented thus far been inadequate, and how can they be addressed? (3) Have those in positions of power done their best to incorporate the communities – human and ecological – that have traditionally been marginalized and excluded from the discourse? Douglas Kelbaugh opens up the issue and the first question by discussing the changing paradigms of urban planning and architecture in light of the challenges of climate change. Mohamed El-Kamel Bakari examines the conflict between the man-nature relationship that the sustainability discourse seeks to engender and the predominant neo-liberal perception of the environment. Savannah Kuper also discusses this relationship, though in the context of anthropocentrism using past philosophical works on the natural world as a framework. Will Evans offers a nuanced critique of the burgeoning fossil fuel divestment movement and challenges the status quo of investment management, which has thus far not been leveraged enough to effect change vis-à-vis damaging corporate activities. Miranda Bernard et al. conducted a study to ascertain how the extinction of mammalian herbivores affected the abundance of five plant species, bringing further light to the profound interconnectivity of natural systems that has undermined elementarist rationality in favor of systems thinking. Finally, Samantha Schipani compares the public and third sectors of Vietnam and Bolivia to consider how they intersect and to challenge the typical roles and priorities of non-governmental organizations. With the second question, we have Tal Cantor et al. assessing the energy efficiency of the kitchen operations of a university to determine opportunities for improvement, while Monica Carty does the same for teaching programs in two developing countries to determine which were most conducive to the long-term success of water projects. Msafiri Daudi Mbaga and Alyssa Menz consider creative solutions to the failings of modern food production, discussing the potential for sustainable desert agriculture in Amman and grasscutter farming in Kenya, respectively. Zachary Davis provides an extensive analysis on the benefits and defects of nuclear power before recommending a course of action for energy; Anthony Ojonimi Onoja conducts a survey on the profitability and issues inherent in contemporary oil palm products’ processing and marketing in Kogi State, Nigeria. Finally, with regards to the third question, Zahra Ahmed et al. discuss the Maasai ethnic group of Kenya and Tanzania and how their culture has transformed with the pressures of climate change, Westernization, and civil institutionalization. Laura Booth et al. attempt to identify the variables that signify changes in elephant diets to determine how climate change will affect elephant populations. Finally, Olivia Winters chronicles the struggles Botswana’s Bushmen to preserve their way of life in the face of an antagonistic Motswana Government. With all of these subjects and their implications, we at Consilience are excited for the year 2015 and the changes that it will bring. We encourage you to continue interacting with the journal through your readership, submissions, and contributions to our Briefings column. As always, we welcome all feedback and hope that our work inspires you to engage with issues trending across the discipline of sustainable development. If you have any questions, comments, or concerns, please do not hesitate to contact us at contact@consiliencejournal.org. We hope you enjoy Issue 13. Ryan Elivo Editor-in-Chief Consilience: The Journal of Sustainable Development January 15, 2015